(untitled) (American Journal of Chemistry and Pharmacy, 2025)
Refractories are non-metallic ceramic materials capable of withstanding temperatures higher than 1500 °C, where the refractoriness is defined by the pyrometric cone equivalent. Silica fume and fly ash are used in industries as cost-effective raw materials to fabricate refractory composites. Mullite ceramic (3Al2O3·2SiO2) is a widely used engineering ceramic material with high strength and high creep resistance at high temperatures, low thermal expansion coefficient, and thermal stability. Cordierite ceramics (Mg2Al4Si5O18) can be used as the carrier of environmental catalysts because of their low coefficient of thermal expansion and stable structure. Therefore, it is an important way to reduce the generation of waste pollutants (Silica fume, fly ash, etc.), reflecting the basic idea of the transformation of solid waste into valuable products. The components of refractory materials are discussed alongside their utilizations, properties, and characteristics.